Pengaruh Struktur Modal Dan Volatilitas Laba terhadap Kualitas Laba PT. Bank Sumut - Aditya Amanda Pane; Sari Nuzullina Rahmadhani (JURNAL AKUNTANSI DAN BISNIS : Jurnal Program Studi Akuntansi, 2021)
The purposes of this research was to determined the influence of the capital structure and earnings volatility on the earnings quality PT. Bank Sumut. This research also aims to assess how the condition of the capital structure, earnings volatility and earnings quality at PT. Bank Sumut for 10 years lately. The proxy of capital structure is leverage, earnings volatility is standard deviasi of earnings and for the earnings quality the proxy is discretionary loan loss provisions. The samples used in this study are the quarterly financial statement of PT. Bank Sumut for the period of 2010 until the first semester of 2020. The analytical method used was multiple regression analysis. The result show that the capital structure has a negative significant effect on the earnings quality and earnings volatility does not has a significant effect on the earnings quality in PT. Bank Sumut. Meanwhile, the capital structure and earnings volatility simultaneous have a significant effect on the earnings quality.